Olfactory Acuity in Chronic Migraine: A Cross‐Sectional Study. Issue 1 (11th November 2014) - Whiting, Alexander C.; Marmura, Michael J.; Hegarty, Sarah E.; Keith, Scott W.
<x xml:space="preserve">Abstract</x> Objective/Background This study aims to measure olfactory acuity in chronic migraine subjects, at baseline and on migraine days, and compare to age‐ and sex‐matched controls. Olfactory impairment is common in neurological disorders. While smell hypersensitivity has been established with chronic migraine, olfactory acuity has not been well studied. Methods We recruited 50 subjects with chronic migraine from the Jefferson Headache Center and 50 age‐ and sex‐matched controls. Using the University of Pennsylvania Smell Identification Test (UPSIT), a validated test of olfaction, olfactory acuity was measured at baseline and during a migraine for subjects, and compared to controls at baseline and at home 2 weeks later. All subjects were additionally screened for odor sensitivity and allodynia. Results The mean UPSIT score for migraine subjects was 34.5 on non‐migraine days and 34.7 on migraine days (mean difference = −0.4, 95% confidence interval [CI; −1.3, 0.6] P = .45). Controls had a mean of 35.9 and 36.1 for each test day (mean difference = −0.1, 95% CI [−0.9, 0.7] P = .87). On average, migraineurs performed worse than their matched control counterparts in both test sittings (test 1: P = .047; test 2: P = .01). The great majority of subjects were allodynic (42/50) compared with only 9 of 50 controls, and the majority of subjects (41/50) found more than one listed odor to be bothersome, compared with only 10/50 controls. On non‐migraine days, 18/48 chronic migraine subjects had abnormal olfaction and on migraine days 14/42 had abnormal olfaction, compared with only 9/50 controls who had abnormal olfaction on their first UPSIT. Conclusions While chronic migraine patients do not appear to have a significant change in olfactory acuity between migrainous and non‐migrainous periods, they do appear to be more likely to have abnormal olfactory acuity at baseline compared to age‐ and sex‐matched controls.